Emergency Exit Guidance for U.S. Highway Tunnels. Issue 1 (2016) - Higgins, Laura; Rozyckie, Stephen; Miles, Jeffrey D.; Carlson, Paul
This research project focused on determining effective messages for encouraging drivers to leave their vehicles and evacuate a tunnel on foot, determining sign and marking formats that most effectively lead people to emergency tunnel exits, and determining the most visible sign and marking materials and technologies for use in highway tunnel environments. Focus groups were conducted to explore potential evacuation messages and delivery methods. Next, a simulated tunnel environment was used to test driver responses to emergency messages and visibility and comprehension of selected emergency exit signs and markings, including the running man symbol prescribed in the ISO 7010 guidelines. The study results highlighted the importance of providing information and instructions to drivers in the event that their vehicles are trapped by an in-tunnel incident. Results also indicated that the running man symbol was correctly or partially understood to indicate an exit by a majority of participants and that a directional sign with the symbol, the word "EXIT, " a directional arrow, and the distance in feet was correctly understood by virtually all participants. Flashing and strobing pathway lighting and audio beacons that indicate the position of exit doors were also favored by test participants. Visibility distances of tested internally illuminated signs were somewhat longer than those of tested photoluminescent signs; visibility for all sign technologies dropped sharply when viewed through smoke.